(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In this article, the lifestyle and culture of the representatives of the Uzbek and Korean people’s diaspora are covered based on the sources, information is provided about the approaches to the study of etymology, the study, development and importance of the Uzbek and Korean people’s traditions with an in-depth comparative study, The purpose of the research is to provide scientific analyzes and conclusions about problems and solutions. Description and analysis of Korean cultural events are given.